ERICH KÄSTNER - ATIVIDADE LITERÁRIA EM PROL DO NEO-OBJETIVISMO E NEO-HUMANISMO - Bossmann, Reinaldo (Revista Letras, 1957)
ERICH KÄSTNER - ATIVIDADE LITERÁRIA EM PROL DO NEO-OBJETIVISMO E NEO-HUMANISMO